Repairing symbolic reparations: assessing the effectiveness of memorialization in the Inter-American System of Human Rights - Greeley, Robin Adèle (International journal of transitional justice, 2020)
The power of memorialization is widely recognized as a form of symbolic reparation aimed at overcoming deep social divisions in the aftermath of mass violence. Yet memorialization as a juridical tool of repair lacks systematic conceptual elaboration, and its potential remains underutilized. This often results in ineffective, even detrimental monuments, and in programmatic failures to integrate memorial practices into multilayered strategies for justice and social reconciliation. This article explores three case studies from the Inter-American Human Rights System in order to examine the strengths and shortcomings of existing approaches to memorialization. We then offer recommendations for expanding the reparative and transformative capacities of symbolic reparations. We conclude by summarizing our observations on how the fundamentally expressive nature of symbolic reparations provides a potentially powerful tool of repair and transformation.